2006
DOI: 10.1097/01.ta.0000197929.74984.1a
|View full text |Cite
|
Sign up to set email alerts
|

Application of Circular External Fixator under Arthroscopic Control in Comminuted Patella Fractures: Technique and Early Results

Abstract: CEF application under arthroscopic control can help avoid some complications of the traditional treatment methods, particularly in comminuted fractures of the patella. The most important advantage of this technique is to allow active knee motion in the early postoperative period so patients can return to activity of daily living soon after the implant removal. In addition, arthroscopic examination of the knee joint provides an assessment of any other intra-articular lesions. This technique allows healing of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 18 publications
0
24
0
Order By: Relevance
“…Yanmis described circular external fixator under arthroscopic control for comminuted patellar fractures. 12 All these articles proved minimally invasive approach could be achieved for transverse patellar fractures. However, the strength of fixation was still a concern.…”
Section: Discussionmentioning
confidence: 97%
“…Yanmis described circular external fixator under arthroscopic control for comminuted patellar fractures. 12 All these articles proved minimally invasive approach could be achieved for transverse patellar fractures. However, the strength of fixation was still a concern.…”
Section: Discussionmentioning
confidence: 97%
“…Open and previously infected fractures are the best candidate for this technique. Yahmis et al [8] described the use of ring external fixation to stabilize the comminuted patella fractures. Big advantage is percutaneously application and in the long term no retained hardware.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported excellent results with arthroscopic fi xation of patellar fractures [ 13,47,49 ] , with all patients achieving union and full functional recovery. The use of a circular external fi xator placed under arthroscopic control has been reported for comminuted fractures of the patella in a small number of patients [ 54 ] ; however patient acceptance might be a problem.…”
Section: Arthroscopic Treatmentmentioning
confidence: 99%